BIOGEOGRAPHIC DIFFERENTIATION OF EPIGEAN FRESHWATER AMPHIPODS (AMPHIPODA: CRUSTACEA) IN BOSNIA AND HERZEGOVINA - Gajević, Mahir; Trožić-Borovac, Sadbera; Mušović, Aldijana; Vesnić, Adi; Đug, Samir (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The inland fauna of epigean freshwater gammarids in Bosnia and Herzegovina is diverse and abundant. This region has a favorable geographical position on the Balkan Peninsula. Excluding Ponto-Caspian species originating in brackish waters and freshwater subterranean taxa, there are 6 formally recognized epigean freshwater species recorded from this country. They belong to 2 genera, from the family Gammaridae, Gammarus 4 species and Echinogammarus 2 species. We provide new data with high-resolution distribution maps, thus improving the knowledge of the ranges of these taxa. Studied species display substantial altitudinal variability and, fragmented distribution. They occur abundantly, particularly in springs and streams, from lowlands to sub-mountainous and mountainous regions. The mosaic distribution of epigean freshwater amphipod species in B&H shows that this region is particularly suitable for biogeographical analyses of this group. Their large-scale distribution patterns remain obscure due to insufficient data, consequently limiting biogeographical interpretations.